(untitled) (LEARNing Landscapes, 2018)
For over 30 years I have been committed to theorizing, interrogating, and practicing life writing as an academic, pedagogical, and curricular discipline. In my life writing I often write what one reviewer called “clichés of the heart.” I wonder what is wrong with clichés. Why are so many people so ready to criticize others for clichés? In an effort to address these kinds of concerns and questions, I offer 13 poetic, narrative, and citational ruminations in defense of clichés. I am eager to understand how clichés are connected to writing about life and learning how to live informed by writing.